Why Are There So Few Women in Executive Positions? An Analysis of Gender Differences in the Life-Cycle of Executive Employment - Anders Frederiksen; Timothy J. Halliday (Institute for the Study of Labor (IZA), 2015)
"Glass ceilings" and "sticky floors" are typical explanations for the low representation of women in top executive positions, but a focus on gender differences in promotions provides only a partial explanation. We consider the life-cycle of executive employment, which allows for a full characterization of the gender composition of executive management. We establish that there are few women in executive management because they have lower levels of human capital, are underrepresented in lower-level jobs, and are less likely to be perceived as high-productivity employees. We do not find that women have uniformly unfavorable promotion and demotion probabilities.
Keywords: J71; J62; 330; discrimination; dynamics; gender